Manoel Bomfim e a educação : interfaces discursivas entre a pedagogia e a psicologia - Negromonte, Fátima Bezerra (2019)
Manoel Bomfim (1868-1932), is today, considered one of the greatest Brazilian historians. Physician, writer, educator, psychologist, and politician, he held relevant positions in the educational field in Rio de Janeiro. He studied Psychology in France in 1902, where he had as his advisors Alfred Binet and George Dumas. He installed, in 1906, the first laboratory of Psychology in Brazil and published books based on his empirical experiences. He was one of the pioneers to converge works in Pedagogy and Psychology in Brazil, subjects little studied at that time. In this perspective, this thesis had as its central question: what were the interfaces between Pedagogy and Psychology in the speeches of the educator Manoel Bomfim? There were also the following related questions: who was the intellectual Manoel Bomfim and what institutional places did he occupy? What was the author-function assumed by Manoel Bomfim in his pedagogical discourses? Based on these questions, the main objective of the research was to analyze the discursive interfaces of Manoel Bomfim in Pedagogy and Psychology. The specific objectives were: to present a profile of Manoel Bomfim and the institutional places he occupied; to identify the author-function assumed by Manoel Bomfim in his pedagogical discourses; to describe the discursive enunciations, mainly taken from his books Lições de Pedagogia (1915) and Noções de Psychologia as well as from two speeches given by the author: the first was entitled The Respect for the Child (1906) and the second, The Moral Person of the Child (Child's Right to Be Educated) (1922). As the methodological procedures of the research, we choose to apply Foucault’s archaeological method of discourse analysis (FOUCAULT, 2005, 2009, 2012). The research pointed out that Bomfim’s intellectual and professional experiences, enabled him to construct educational discourses related to the principles of Psychology. He provided his students from the Normal School of Rio de Janeiro with scientific knowledge from Pedagogy and Psychology in order to enable them to understand the child's development processes and their relationships with the social environment and the learning acquisition, aiming, therefore, to establish conditions for the future primary school teachers to develop pedagogical skills and competencies, according to the most modern studies at that historical moment. He first produced the textbooks to elementary school children and, only later, he wrote theoretical compendiums for students in teaching training. The pedagogical propositions of the author were, mainly, related to the Functionalist School, which was based in the evolutionary theory of Charles Darwin (1809-1882). His speeches demanded for pedagogical practices established in democratic and humanistic principles. According to his beliefs, Education was the only vehicle that would lead the country to the so called “civilization”.